The challenges faced by the nurse of the intensive care unit in the treatment of patients with Covid-19: An integrative literature - Cortez, Eduardo Nogueira; De Oliveira Júnior, Wander Valadares; Souza, Ariane Caroline De Miranda; Ferreira, Flaviana Aparecida Carvalho; Abreu, Jéssica Beatriz Maia; Souza, Lívia Fernandes (Seven Editora, 2023)
Objective: to highlight the main challenges faced by nurses in the intensive care unit in the treatment of patients affected by covid-19. Method: integrative literature review, operationalized in the scientific electronic library online databases, database on nursing, sus collection and latin american and caribbean literature on health sciences. Results: through a search of the chosen descriptors, 14 articles were selected from a sample of 403. 3 main axes of analysis were categorized: challenges related to structural issues of the icu environment, environmental challenges related to the hospital environment and psychosocial challenges related to the nursing profession applied to the covid icu. Conclusion: there are structural and psychosocial factors that impact the nursing service in the icu, and these factors need to be mitigated to improve the quality of life and health of professionals, and consequently to improve health care. DOI:https://doi.org/10.56238/emerrelcovid19-021